OPTIMALISASI PRODUKSI MENGGUNAKAN METODE INTEGER PREEMPTIVE GOAL PROGRAMMING (Studi Kasus: UD Citra Ayu Bali) - ROSSARY, VINSENTIA REVICA BELLA; SUMARJAYA, I WAYAN; SARI, KARTIKA (E-Jurnal Matematika, 2019)
One of the home industry in Bali that produces beauty products is UD Citra Ayu Bali. This company has five types of body scrub scent, where the five types of body scrub has a different number of requests. UD Citra Ayu Bali has been doing production activities only when there is demand, so the production process is still less than optimal because it is still done randomly or unplanned. Therefore, this research is done to make production planning body scrub UD Citra Ayu Bali by determining the prediction of the number of products that must be produced every week so that the production process becomes optimal. By using the integer preemptive goal programming method, the optimal production number of the five types scrubs for 12 consecutive weeks is 212 pieces, 548 pieces, 328 pieces, 474 pieces, 506 pieces, 455 pieces, 103 pieces, 381 pieces, 63 pieces, 547 pieces, 59 pieces, and 454 pieces.